Estimation of Daily Evaporation from Calculated Evapotranspiration in Iraq - Hussain Zaydan Ali; Saad H. Faraj (Journal of Madenat Alelem University College, 2017)
The knowledge of the evapotranspiration (ET) of natural ecosystems and plant populations is of fundamental importance in several branches of science, research and practical uses. Calculation of total daily Evaporation related to calculate the loss of water by daily evapotranspiration from FAO Penman-Monteith equation. Twenty two climatological stations are used in this work for the period 2004-2013 in Iraq. Estimating conversion constant in order to calculate Evaporation value and comparing it with measured value from Iraqi meteorological organization and seismology. The results show high correlation coefficient. We formulated method is proposed to for calculate the amount of evaporation for missing data of climatological Iraqi stations from calculated evapotranspiration value. GIS maps reflect distribution of evaporation, evapotranspiration and Kp in Iraq.